2018
DOI: 10.1017/s1748499518000301
|View full text |Cite
|
Sign up to set email alerts
|

A review of global banking regulation under an assumption of complexity

Abstract: The global banking system can be shown to be a Complex Adaptive System that exhibits phase transitions from time to time. These phase transitions can result in significant financial losses to the community that we estimate to be much more significant than losses occurring during “business as usual” periods. In this paper, we argue that the significant losses arising from phase transitions in the banking system requires a very different approach to regulation than the current Basel regime, and that there is a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…The first group of proposals focuses on the improvements of the current system, whereas the other suggests implementing new approaches to banking system regulation and supervision. Evans and Li (2019) highlight the need for significant changes in the current international regulatory and supervisory architecture based on the Basel Committee of Banking Supervision. Farmer et al (2012) suggest orienting the management of the financial markets around the approach that links these markets with real economy and macroeconomic modelling and better understanding the processes in the real economy which lead to financial crises.…”
Section: The Reaction Of the System And The Escalation Effectmentioning
confidence: 99%
“…The first group of proposals focuses on the improvements of the current system, whereas the other suggests implementing new approaches to banking system regulation and supervision. Evans and Li (2019) highlight the need for significant changes in the current international regulatory and supervisory architecture based on the Basel Committee of Banking Supervision. Farmer et al (2012) suggest orienting the management of the financial markets around the approach that links these markets with real economy and macroeconomic modelling and better understanding the processes in the real economy which lead to financial crises.…”
Section: The Reaction Of the System And The Escalation Effectmentioning
confidence: 99%
“…The financial industry also has no central control as was recognised as early as Adam Smith (1776) when he talked about “an invisible hand” operating in the markets. Similarly, in the financial industry, there is no global control for the trading activities of participants, and regulators are concerned only with specific geographic areas as shown by Evans & Li (2018 a ) who demonstrated that the global banking system was a federation of systems (FOS) 1 . It is relatively easy to observe the emergent property of a CAS in the financial industry as it is impossible to predict the market change by observing one or two financial institutions.…”
Section: Similarities Of Biological and Financial Systemsmentioning
confidence: 99%
“…Song & Thakor (2010) found that co-evolution in banks was generated by the effect of including securitisation of other banks’ assets in bank equity capital. Evans & Li (2018 a ) argued that the extent of the interdependence of the global banking system was so high as to require a change in the regulation of banks from an FOS to an SOS basis. The above discussion leads to the conclusion that the global financial system presents the essential characteristics of a CAS, that is, numerous agents, interactions among agents, no central control and emergence.…”
Section: Similarities Of Biological and Financial Systemsmentioning
confidence: 99%